Situation Report: Baltic Area, 7 July 1989 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Estonian Communist Party Condemns 1941 Deportations / by Velo Pettal Monument to Interwar President Dedicated / by Velo Pettal Estonian Citizens' Committees to Organize Congress of Estonian Citizens / by Velo Pettal Leaders of the People's Front of Latvia Call for Independence / by Dzintra Bungs Latvia in May 1989: Thinking of Independence / by Dzintra Bungs Successful Baltic Protest against a Committee for Constitutional Supervision / by Saulius Girnius